2014
DOI: 10.3748/wjg.v20.i33.11780
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of monocarboxylate transporter activity in hepatocellular carcinoma

Abstract: MCT4 and GLUT1 appear to play a role in HCC progression, while MCT2 is lost during progression and associated with better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…18 Interestingly, MCT2 cytoplasmic expression has already been associated with variables related to a less aggressive profile of hepatocellular carcinomas. 44 In this study, we observed that MCT2 was significantly associated with well-differentiated tumors.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…18 Interestingly, MCT2 cytoplasmic expression has already been associated with variables related to a less aggressive profile of hepatocellular carcinomas. 44 In this study, we observed that MCT2 was significantly associated with well-differentiated tumors.…”
Section: Discussionmentioning
confidence: 60%
“…25 In the present study, there was no association between MCT4 and overall survival. Since MCT2 expression was associated with good prognostic variables in other types of cancers 34,44 and in contrast to MCT1 and MCT4, is mainly responsible for the uptake of monocarboxylates into cells, 18 we analyzed tumors that express both MCT1 and MCT4, as these are the isoforms correlated with the hyperglycolytic phenotype, and were negative for MCT2. Although we did not find any association with the different clinicopatological data, interestingly, we observed that MCT1 (C)/MCT4(C)/MCT2(¡) tumors have a shorter overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, corpses are refrigerated and medical autopsies are performed as soon as all technical and legal procedures are addressed and resolved. Nevertheless, we sought to minimize the effects of autolytic changes by excluding samples with morphological features of poor preservation, specifically by examining vimentin staining (comparing to positive and negative controls) to assure that protein preservation was good enough to yield reliable immunohistochemical studies [34] .…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with HCC progression and poor prognosis[48,49]. The latest study observed the reduced expression of MCT1 and MCT2 in HCC[50]. However, the data from another study showed that MCT1 was over-expressed in HCC cells which facilitates the lactate exporting and promotes HCC glycolysis[51].…”
Section: Reprogramming Of Glucose Metabolism-related Enzymes and Tranmentioning
confidence: 99%